2020
DOI: 10.1017/s0144686x20001282
|View full text |Cite
|
Sign up to set email alerts
|

Older adults’ accounts of the relationships between retirement timing and health: a descriptive qualitative analysis in Chile

Abstract: Retirement timing can have important health implications. Little is known, however, about older adults’ views on this issue and whether they consider it better to retire later, earlier, on time or anytime. This knowledge gap about older adults’ views is particularly true outside North America and Europe. This qualitative study aims to examine older Chileans’ ideas about the relationship between retirement timing and health and to explore gender and class patterns in qualitative themes identified, knowledge whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…The active ageing approach refers to older adults' participation in diverse areas, including economic, social or spiritual affairs, thus moving from a passive and dependent way of life in old age towards an engaged and dynamic lifestyle (Foster and Walker, 2013;Foster, 2018). Further, several studies found that staying economically active beyond legal retirement age can promote the physical, mental and social wellbeing of older adults (Rohwedder and Willis, 2010;Shura et al, 2022), an idea that is also reinforced in one of the latest works by Phillipson (2022). Therefore, an active ageing approach with its particular focus on older adults' economic activities can facilitate a better understanding of extended careers, challenges and opportunities encountered by an ageing population in this regard (Foster and Walker, 2013).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The active ageing approach refers to older adults' participation in diverse areas, including economic, social or spiritual affairs, thus moving from a passive and dependent way of life in old age towards an engaged and dynamic lifestyle (Foster and Walker, 2013;Foster, 2018). Further, several studies found that staying economically active beyond legal retirement age can promote the physical, mental and social wellbeing of older adults (Rohwedder and Willis, 2010;Shura et al, 2022), an idea that is also reinforced in one of the latest works by Phillipson (2022). Therefore, an active ageing approach with its particular focus on older adults' economic activities can facilitate a better understanding of extended careers, challenges and opportunities encountered by an ageing population in this regard (Foster and Walker, 2013).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Descriptive analysis is also very often used in social sciences (18.56%). Scientists in this field are currently studying some aspects based on descriptive analysis, which include a descriptive analysis of complaints related to COVID-19 in California by Thomas M. D. et al [62]; a descriptive qualitative analysis of older adults' accounts in Chile by Shura R. et al [63]; and others such as Njegovanovic A. [64], Sarihasan I. et al [65], Pop R.-A.…”
Section: Introductionmentioning
confidence: 99%
“…Known factors associated with being active in working life after the expected retirement age include a higher educational level, working within highly skilled occupations/professions, good health status, and being male [ 6 , 7 , 8 , 9 ]. Qualitative studies have revealed that perquisites and motivations for working life after the expected retirement age can include work satisfaction and good organizational support [ 10 , 11 , 12 , 13 , 14 , 15 ], financial incentives [ 13 , 14 , 15 , 16 , 17 ], social benefits [ 11 , 15 , 16 ], and/or having flexibility in work, e.g., time or tasks [ 14 , 15 , 16 , 18 ]. Earlier research has also shown that both managers [ 15 , 19 ] and workers [ 15 , 20 ] highlight good health as a key facilitator to an extended working life.…”
Section: Introductionmentioning
confidence: 99%